Factors affecting utilization of male sexual and reproductive health services: a qualitative description of males in Anambra State, Southeast Nigeria - Nwamaka Alexandra Ezeonu; Nkiru Nwamaka Ezeama; Ijeoma Uchenna Itanyi; Jane Nkolika Ezeonu; Achunam Simeon Nwabueze (BMC Public Health)
Abstract Introduction The utilization of sexual and reproductive health (SRH) services by males globally is significantly low despite their considerable sexual and reproductive health needs. This study aimed to understand the factors that influence the utilization of male sexual and reproductive health SRH services. Methods We used an explanatory sequential mixed methods research design, with qualitative description to explore the perceptions of males (15-49years) on the utilization of male SRH services in Anambra State, Nigeria. In October 2021, 56 males participated in seven focus group discussions conducted across seven communities. The data were analysed by thematic analysis. A composite narrative was used to report the results. Results Males in both urban and rural areas of Anambra State preferred informal health facilities; male-focused health facilities and male health workers. The participants perceived services as costly; and criticized healthcare workers’ attitudes. Some rural areas had inadequate SRH facilities, staff and commodities. The participants exhibited varying levels of SRH awareness. Conclusion To improve male SRH service utilization, clinics should be more male-centric and cost-effective. Healthcare providers require retraining to offer patient-centered care. Additionally, ward development committees should advocate for better staffing and the availability of SRH commodities.